Centers and Peripheries in Romance Language Literatures in the Americas and Africa (Brill, 2024)
What is center and periphery? How can centers and peripheries be recognized by their ontological and axiological features? How does the axiological saturation of a literary field condition aesthetics? How did these factors transform center-periphery relationships to the former metropolises of Romance literatures of the Americas and Africa? What are the consequences of various deperipheralization contexts and processes for poetics? Using theoretical sections and case studies, this book surveys and investigates the limits of globalization. Through explorations of the intercultural dynamics, the aesthetic contributions of former peripheries are examined in terms of the transformative nature of peripheries on centralities.